2022
DOI: 10.1111/jcmm.17511
|View full text |Cite
|
Sign up to set email alerts
|

tRNA‐derived fragments in gastric cancer: Biomarkers and functions

Abstract: tRNA‐derived fragments (tRFs), non‐coding RNAs that regulate protein expression after transcription, have recently been identified as potential biomarkers. We identified differentially expressed tRFs in gastric cancer (GC) and the biological properties of tRFs in predicting the malignancy status of GCs as possible biomarkers. Until 15 February 2022, two independent reviewers did a thorough search in electronic databases of Scopus, EMBASE and PubMed. The QUADAS scale was used for quality assessment of the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…16 Another study revealed the advances of tRFs in GC and their functions in gene expression regulation and the related signal transduction pathways associated with them. 17 On the basis of the previous and present study, we believe that PGI and G-17 are valuable for differentiating EGC and gastric IN. However, the small number of samples and operator error might have influence on the accuracy of the result.…”
Section: (supporting
confidence: 59%
“…16 Another study revealed the advances of tRFs in GC and their functions in gene expression regulation and the related signal transduction pathways associated with them. 17 On the basis of the previous and present study, we believe that PGI and G-17 are valuable for differentiating EGC and gastric IN. However, the small number of samples and operator error might have influence on the accuracy of the result.…”
Section: (supporting
confidence: 59%
“…When tRNA is not sufficiently modified, tRNA stability could be disrupted and cleaved to tRFs or degraded by Dicer, endonuclease Z (RNase Z/ELAC2) and other RNA endonucleases (RNases) [ 15 17 ]. tRFs/tiRNAs are categorized into five types based on their cleavage sites on mature tRNA by different nucleases, including 5’-half, 3’-half, 5’-tRF, 3’-tRF, and i-tRF [ 18 20 ]. Among them, 5’-half and 3’-half are usually produced under various stress conditions in cells, generated by the activation of angiogenin (ANG) enzyme activity, which cleaves tRNA at the anticodon site [ 21 , 22 ].…”
Section: Trna Biological Functionmentioning
confidence: 99%
“…The authors developed a GC diagnostic model containing three tRFs (tRF-52:76-Val-AAC-1-M3, tRF-59:76-Val-AAC-1-M5, and tsRNA-39:74-tRNA-Val-AAC-1-M3) with a mean AUC of 0.815, demonstrating greater sensitivity and specificity for GC diagnosis than the commonly used clinical markers and each of the three tRF biomarkers. The results suggested that plasma exosome tRF-52:76-Val-AAC-1-M3, tRF-59:76-Val-AAC-1-M5, and tsRNA-39:74-tRNA-Val-AAC-1-M3 are biomarkers for GC diagnosis and prognosis and help to identify and diagnose GC patients with a high risk of recurrence and poor prognosis ( 31 , 62 ).…”
Section: Roles Of Tsrnas In Gastric Cancermentioning
confidence: 99%